P-012 ESTABLISHING THE NORTH-WEST LONDON MDT FOR COMPLEX ABDOMINAL RECONSTRUCTION: OUR EXPERIENCE. (13th October 2022) - Grove, T; Howell, A M; Kontovounisios, C; Nicolay, C; Mehta, A; Warren, O
Abstract: Aim: Complex patients have been shown to have favourable outcomes when managed under the care of the multi-disciplinary teams (MDT) 1, 2 . In 2019 we published our experience of a single centre complex AWH MDT and advocated its use 3 in line with EHS and a collaborative group from AWRE 2020 4, 5 . Expansion: Further development has led to the set-up of a regional, tertiary, complex, abdominal wall reconstruction MDT service. This has facilitated identification of patients who will ultimately benefit from management of the regional AWH MDT surgical teams undertaking the most complex of abdominal wall procedures together. Since 2021 our regional MDT discussed 87 cases including tertiary referrals from within and out with the immediate geographical area. 71 abdominal wall hernias including 15 recurrent, 6 with concurrent parastomal hernias, 9 parastomal hernias and one perineal hernia. Progression: The development of virtual conferencing services has allowed the MDT improved access for healthcare professionals. With resources for benign cases becoming increasing restricted, having an MDT approved management plan for patients streamlines services and allows costs to be rationalised. Scheduling joint operations between different hospitals facilitates pooling of expertise for difficult cases. We are developing an online registry for involved abdominal wall units to allow data sharing, service evaluation and improve accountability. Conclusion: Appreciation of complex abdominal wall surgery as a stand-alone sub-specialty is increasing and there is a consensus among hernia surgeons that these patients should be managed by the MDT in specialist centres by specialist surgeons enhancing learning, proficiency, and accountability.